Terrenos de marinha : antecedentes, invenção e atualidades - Dantas, Fernando Luís Lopes (2019)
The naval coastal lands, since when invented by the Law Decree of January 21, 1809 (only so designated by the Notice of July 7, 1829), are involved in tensions and they have been subject to questioning, a finding revealed by the existence of legislative projects aimed at changing the legal regime or even the extinction of this category of goods. The Union, defensing the institute, believes that its existence and the maintenance of its legal system would be imperative measures, because supposedly conformed to the triad of values corresponding what has been called the “sustainability tripod”, signed in environmental, social and economic aspects. In order to contribute to this debate, the general objective of this research was to elaborate a history to the naval coastal lands, informed by a genealogical character which the analyses are centered on the possibility invention conditions and the naval coastal lands keeping, and the problematization of their social function (“Socioenvironmental”). To this work, it was proposed an approach called Archeogenealogy “from” Foucault, elaborated by composite elements from the Foucault’s Archeology and Genealogy. The dissertation is structured in three development chapters, beyond the Introduction and Conclusion (“Presents Considerations”). The first chapter comprises the elaboration of the proposed approach (Archeogenealogy from Foucault) and the presentation of the research related to methodological, procedural and theoretical aspects. The second one is related to the description and the practices analyses (discursive and non-discursive) that help the invention of the naval coastal lands, in other words their sociohistorical conditions of possibility. The third produced “to” (the) description and analyses of the institute historical "journey", from its invention in 1809 to the present. This chapter also problematized the naval coastal lands social function, choosing for a thematic cut, which considered the practices rather than the chronological time linear orientation. Finally, in the “Present Considerations”, a synthesis of the work was created, which the conclusions that the synthesis effort imposes would be: a) the history is an invention produced through the several power relations; b) the property, as fact and as right, is a historical category and, therefore, invented; c) the notion of social function idealizes the “social” element of this concept, although hidden this condition with the intention subjecting the society to the elite instead who has the power to decisively influence the legal rules production; d) the public ownership in Brazil was produced by the colonial device required by the Portuguese Crown, with force and domination discursive elements, removed from the territory the natives who had lived here before the year 1500; e) since its inception, the normative discipline was created with the purpose to manage the real estate property according to economic interests, enabling its appropriation based on census (leather) and excluding or making difficult the access to the land for people who had no financial resources; f) naval coastal lands, according this same logic of agency, were invented and exist nowadays as an instrument to privileged spaces appropriation in favor who can pay more for them, which take to confirmation, as the main conclusion to this dissertation, of the lament that was sung by Caetano, when "the power of money (...) raises and destroys beautiful things".